Faktor-Faktor Yang Mempengaruhi Perilaku Seksual Remaja Di SMP Negeri 02 Kota Bengkulu - Widiyanti, Desi (JURNAL BESUREK JIDAN, 2024)
Adolescent sexual behavior is all types of adolescent behavior that is driven by sexual desire, both with the opposite sex and the same sex. Based on data from the World Health Organization, 40% of adolescent girls have sex without marriage. Sexual behavior that is as the age of puberty, parenting parents, peers, and information media. The purpose of this study was to determine the factors that influence adolescent sexual behavior. The research design used in this study is an analytical survey research method with a cross-sectional research design. With a population of 166 students, the sample of this study was 118 female students of class VIII with a sampling technique using stratified random sampling. Data analysis used univariate, bivariate, and multivariate analysis. Studyl results show that there is an influence between the factors of puberty age (p-value = 0.031), peers (p-value = 0.003), and there is no influence on parenting style (p-value = 1,000), Information media (p-value = 0.981) on sexual behavior. Peers are the most dominant factor influencing adolescent sexual behavior. It is hoped that the school can increase the knowledge of students of SMP Negeri 02 Bengkulu City, especially about the factors that influence adolescent sexual behavior in PIK-R activities. Keywords: age of puberty, parenting parents, peers, information media, sexual behavior